FPGA-based embedded architecture for IoT home automation application - Chee-Pun Ooi; Wooi-Haw Tan; Soon-Nyean Cheong; Yee-Lien Lee; V. M. Baskaran; Yeong-Liang Low (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
An Internet of Things (IoT) FPGA-based home hub to automate control operations in a home environment was designed and built. The proposed system uses an FPGA home hub as its local analytic engine with an IoT platform to store the sensory data. The FPGA was programmed in Verilog HDL using Quartus II provided by Altera. The WiFi capability of the FPGA was extended through an ESP8266 chip to ease the interfacing with various sensors connected to it. The system can be configured and monitored through a web application coded in JavaScript. Various test cases were carried out on the implemented system at Multimedia University (MMU) Digital Home Lab. The results verified the functionality of the system in triggering real home appliances (i.e. air conditioning unit and lighting) based on multiple sensor nodes without conflicting each other. The ability to allow user to configure the control rules based on the sensory data via web interface hosted using ThingSpeak Plugins is also presented and demonstrated in this project. The base design is utilizing Altera Cyclone IV EP4CE22F17C6N FPGA with 153 I/O pins, which is highly scalable and adaptable to the requirements of home environments. This shows promising application of FPGA in supporting scalable IoT home automation system.